2020
DOI: 10.1101/2020.06.29.20142455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple Myeloma and SARS-CoV-2 Infection: Clinical Characteristics and Prognostic Factors of Inpatient Mortality

Abstract: There is limited information on the characteristics, pre-admission prognostic factors, and outcomes of patients with multiple myeloma (MM) hospitalized with coronavirus disease 2019 (COVID-19). This retrospective case series investigated characteristics and outcomes of 167 MM patients hospitalized with COVID-19 reported from 73 hospitals within the Spanish Myeloma Collaborative Group network in Spain between March 1 and April 30, 2020. Outcomes were compared with a randomly selected contemporary cohort of 167 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 30 publications
(44 reference statements)
0
46
2
Order By: Relevance
“…Our data suggests higher mortality in hospitalized patients with MM and COVID-19 infection than non-myeloma patients. A recent study from Spain found higher mortality rate in MM patients with COVID-19 (34%) compared to age and sex matched non-MM patients with COVID-19 (23%) 21 . A recent publication from France confirmed overall mortality in all hospitalized patients with COVID-19 to be 16%, which is significantly lower then mortality observed in hospitalized MM patients in France (39%) 22 .…”
Section: Discussionmentioning
confidence: 90%
“…Our data suggests higher mortality in hospitalized patients with MM and COVID-19 infection than non-myeloma patients. A recent study from Spain found higher mortality rate in MM patients with COVID-19 (34%) compared to age and sex matched non-MM patients with COVID-19 (23%) 21 . A recent publication from France confirmed overall mortality in all hospitalized patients with COVID-19 to be 16%, which is significantly lower then mortality observed in hospitalized MM patients in France (39%) 22 .…”
Section: Discussionmentioning
confidence: 90%
“…[ 26 ] Preprint 181 60 30 Apr to 26 May 2020 Brazilian National Cancer Institute Any 19 Martinez-Lopez et al. [ 27 ] Preprint 167 56 1 Mar to 30 Apr 2020 73 hospitals in Spain Multiple myeloma only 20 Russel et al. [ 28 ] Preprint 156 34 29 Feb to 12 May 2020 Guys Hospital, London, UK Any 21 Basse et al.…”
Section: Resultsmentioning
confidence: 99%
“…We did not collect data on contacts although during the first wave of the COVID-19 pandemic in Madrid, we expected most patients to be infected by community transmission. Finally, our case series incorporates a heterogeneous patient population with multiple different hematologic malignancies; further studies in patients with specific malignancies [32] are needed, as it is possible that type of malignancy and disease status may affect the clinical course of COVID-19. Nevertheless, our study included a large number of patients with some malignancies, which could overcome in part this perceived limitation.…”
Section: Limitationsmentioning
confidence: 99%